Viale delle Belle Arte
View of masonry retaining wall, pedestrian path. World Heritage Site. Residents (likely farmers & fishermen) formed a large pile of rubble & consolidated rubbish, then dug into it to create dwellings & passageways. Family dwellings were generally circular with hearth at center & hole in roof & connected to others with narrow, curving passageways. Dwellings in close proximity, connected by curving, narrow passageways. Mainland=largest island of the Orkneys